Deep learning as a bridge between intercultural sensitivity and learning outcomes: A comparative study of English-medium instruction delivery modes in Chinese higher education - Qian Long; Shengbing Li; Ran An; Fakhra Yasmin; Ahsan Akbar (Acta Psychologica)
With the advancement of digitalization and blended learning, the integration of internationalization and technology has become increasingly significant in the context of English-medium Instruction (EMI). Both in-person and live online EMI courses delivered by foreign teachers (EMI-FT) have emerged as key components of Chinese universities' internationalization strategies. EMI refers to the use of English to teach academic subjects in non-English-speaking countries, exposing students to the challenges of intercultural learning and communication. Prior research indicates that such environments often provoke emotional disturbances, especially in virtual settings where interpersonal engagement is limited. As an essential component of intercultural competence, intercultural sensitivity (IS) is believed to play a crucial role in enhancing students' ability to adapt and succeed in EMI-FT environments. Specifically, IS may influence deep learning (DL), which promotes a deeper understanding and the application of knowledge. However, existing studies have rarely examined how IS affects students' learning experiences and outcomes in both in-person and online EMI-FT contexts. Guided by Biggs' 3P (Presage–Process–Product) model, our study constructs a mediation framework to investigate the relationships among IS, DL, and learning outcomes (LO) across both delivery modes. Data were collected using self-reported instruments from 1192 students across five universities in southern China. The results revealed that: (1) students perceived live online EMI-FT as less effective than in-person EMI-FT in promoting DL and LO; (2) IS was positively associated with both DL and LO; (3) DL mediated the relationship between IS and LO, with a more substantial mediation effect in the online setting; and (4) multi-group analysis revealed significant differences in the IS–DL–LO pathways between in-person and online samples. These findings offer actionable insights for universities seeking to tailor EMI-FT strategies to enhance student engagement and learning across diverse instructional formats.